Readiness For Development of Tourism Villages in Pangkalpinang City - Valeriani, Devi; Wulandari, Ayu; Nurwasya, Nurwasya; Marlina, Marlina (Jurnal Penelitian Pariwisata, 2024)
This research analyzes the readiness of Tourism Village Development in Pangkalpinang City by identifying the potential and readiness of tourist village components consisting of tourist attractions, accessibility, amenities, supporting facilities and tourism institutions, marketing and community participation. This research uses a qualitative approach with evaluative and stakeholder analysis. The data in this research was taken through interviews and observation carried out in three areas, namely Kampung Tua Tunu, Kampung Jerambah Gantung and Kampung Selindung. Using a purposive sampling method, the respondents in this research were the government, private sector and the community from each village. The results of this research show that Kampung Tua Tunu is categorized as an embryonic tourism village with stakeholders classified as Key Players and Crowd of four respondents each, stakeholders classified as Context Setters as many as one respondent and there are no stakeholders as Subjects. Jerambah Gantung Village is categorized as an embryonic tourism village with stakeholders classified as Key Players totaling four respondents, stakeholders classified as Subject and crowd each with three respondents and there are no stakeholders as Context Setters. Then Selindung Village is categorized as a Developing Tourism Village with nine respondents classified as Key Players and the remaining one respondent is a stakeholder classified as Subject. Keywords: readiness, potential, tourism village